(3QSGdg GdCSWQdGHs - (3CejI Hf YHO GdYRjR GdCfOdSj, CHh GdUdJ,J (B529 (3g` s ((3eMeO Hf ZGdH Hf eMeO GdGhRGYi s)
(3ChdgG (B:s
(3HYO GdOjHGLg gfG cJGH jJVef ef CHhGH GdYde ai GdGSWQdGH eGdGHO efg hdGZfi YfgG s
(3BNQgG (B:s
(3aeG MUd HYO GdPjGOg hGdfbUGf agh YOO CLRGA GdSjQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B52 - (3U(B92s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B486 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B39 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3482(6)) s
Keywords: (3Gdadcs